Effect of Laser and Intense Pulsed Light in treatment of hirsutism in women with polycystic ovary syndrome (PCOS): A systematic review - Marzieh Saei Ghare Naz; Fahimeh Ramezani Tehrani (Mashhad University of Medical Sciences, 2020)
Introduction: During recent decades, laser therapy has been one of the most popular methods in treatment of hirsutism in women with polycystic ovary syndrome (PCOS). This study was performed with aim to determine the therapeutic effect of laser on hirsutism in women with PCOS as a systematic review. Methods: The search process of experimental and semi-experimental studies (Persian and English language) was performed in databases including PubMed, Scopus, Web of Science, Cochrane library, Magiran, SID, and IranDoc up to July 2020. The search was performed using the keywords of polycystic ovary syndrome, hirsutism, laser, treatment, hair, and the related latin keywords. The main outcomes were the effect of interventions on hair loss, hair loss duration, the duration of new hair growth, and the side effects of laser treatment. Results: After the advanced search, 11 articles (638 participants) had inclusion criteria. The skin type of the participants was based on Fitzpatrick scale. The majority of studies used the Alexandrite laser device. The duration of treatment in the studies was a maximum of 6 months with treatment intervals of 4 to 6 weeks. The main outcomes of this study included: significant reduction in the number of hairs and the intensity of excess hair, an increase in the mean growth time of new hair, energy levels in the range of 10 to 50 j/cm2 and duration of 20-50 milliseconds. The complications included hyperpigmentation, erythema, and pain. Conclusion: The findings indicated the impact of light-based technologies on different types of outcomes associated with the treatment of hirsutism in women with PCOS, but due to the limitations, there is no consensus on the most appropriate type of laser, fluorescence, and the number of treatment sessions. Greater clinical trial studies are needed to develop the clinical guidelines.